If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x + 15 = x + 45 + x + 40 + x + 25 Reorder the terms: 15 + x + x = x + 45 + x + 40 + x + 25 Combine like terms: x + x = 2x 15 + 2x = x + 45 + x + 40 + x + 25 Reorder the terms: 15 + 2x = 45 + 40 + 25 + x + x + x Combine like terms: 45 + 40 = 85 15 + 2x = 85 + 25 + x + x + x Combine like terms: 85 + 25 = 110 15 + 2x = 110 + x + x + x Combine like terms: x + x = 2x 15 + 2x = 110 + 2x + x Combine like terms: 2x + x = 3x 15 + 2x = 110 + 3x Solving 15 + 2x = 110 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 15 + 2x + -3x = 110 + 3x + -3x Combine like terms: 2x + -3x = -1x 15 + -1x = 110 + 3x + -3x Combine like terms: 3x + -3x = 0 15 + -1x = 110 + 0 15 + -1x = 110 Add '-15' to each side of the equation. 15 + -15 + -1x = 110 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = 110 + -15 -1x = 110 + -15 Combine like terms: 110 + -15 = 95 -1x = 95 Divide each side by '-1'. x = -95 Simplifying x = -95
| 7z+10-4z=8+2z+10 | | y-13/23=-5/23 | | 6-1/2x=3/5 | | 2x-(x+2)-(x-2)=x-10 | | 2(n-3)-(4-5n)=6n | | f+-63=27 | | 5x^3-3x^2=2 | | (8x+7)(x-4)=0 | | -16(y+1)+5(4y-4)=3(y-3)+10 | | 4q+2=3q-2 | | 57.99-0.11d=58.54 | | 28x-4+6-15x-12x-20=-6 | | 7b+2b=63 | | 2x+15=3x+110 | | 5(7+w)=4(6+w) | | 12a^3x^2-6a^2x^4/6a^3x^2 | | 10(3x-2)=5(2-x) | | -3(x+5)=5x-(3+2x) | | t-7= -7 | | 4(6-x)=10 | | 4k=76 | | m=n/16 | | 17x-(7x-5)-(7000-20000)-49000=0 | | y=(6x+1)(x-5) | | 5(3c+2)+4(2c+1)= | | 4x-3=4x-5 | | 7.2x+2=6.2x | | 15f=k(k-f)+7+8f | | 1x+45=2x-2 | | (40x+16/6)/(20x+8/6x) | | 88=n+81 | | u+32=99 |